Significance Of Right Ventricular Diastolic Dysfunction in Patients with Hypertension (Eurasian Medical Research Periodical, 2022)
Hypertension is currently one of the most urgent medical problems. This is largely due to the fact that arterial hypertension, which largely determines the high cardiovascular morbidity, disability and mortality, is also characterized by a wide prevalence. Early diagnosis of changes in the heart in patients with hypertension is of great practical interest, which allows timely preventive measures and treatment